2021
DOI: 10.1177/2321022221995674
|View full text |Cite
|
Sign up to set email alerts
|

Gender Pay Gap in India: A Reality and the Way Forward—An Empirical Approach Using Quantile Regression Technique

Abstract: There is a growing body of empirical work on gender studies that mostly focus on the gender-wise representation of individuals in different sectors. One such study is the wage gap attributed to gender. In this article, we have tried to focus on a detailed study of the gender wage gap in the Indian context. The study was carried out on the most recent Employment–Unemployment Survey carried out by NSS for the year 2012. The study was based on the personal characteristics as well as the characteristics of the job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
3
2
0
Order By: Relevance
“…We found that an individual's education level, years of work experience, household financial background, and marital status significantly affect their wage in both rural and urban areas. This is line with human capital theory of wage determination Becker (2009) as well as Sengupta & Puri (2022) who attributed the wage differential to personal factors for India. We further find that the log wage differential decreased between 2005 and 2011 at the national, rural, and urban levels, consistent with Bhattacharjee et al (2015) findings.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found that an individual's education level, years of work experience, household financial background, and marital status significantly affect their wage in both rural and urban areas. This is line with human capital theory of wage determination Becker (2009) as well as Sengupta & Puri (2022) who attributed the wage differential to personal factors for India. We further find that the log wage differential decreased between 2005 and 2011 at the national, rural, and urban levels, consistent with Bhattacharjee et al (2015) findings.…”
Section: Discussionsupporting
confidence: 88%
“…We observe that a larger proportion of the wage differential is due to unobservable/unexplained reasons for all three categories considered in both 2005 and 2011. This aligns with existing literature and supports the claim that differences in wages in the Indian labor market are largely due to discrimination rather than differences in ability (Sengupta & Puri 2022). Notably, for both years, rural areas account for a distinctly higher proportion of the wage gap due to unexplained reasons-72.20 percent in 2005 and 83.50 percent in 2011.…”
Section: Blinder-oaxaca Decompositionsupporting
confidence: 89%
See 1 more Smart Citation
“…In comparison to their male counterparts, it is harder for women who do find employment to obtain acceptable compensation. Sengupta and Puri (2022) further observed a continuous, significant increase in gender pay gap in India during 1999-2012.…”
Section: Introductionmentioning
confidence: 88%
“…Policies enforcing gender parity and equal pay for equal labour at all organisational levels intend to create a gender-neutral society over a patriarchal society. India is also experiencing such changes in its socioeconomic policies, and there have been some encouraging advancements in the last 20 years regarding gender equality at work and in payment (Bennedsen et al, 2023;Dhar-Bhattacharjee & Dwivedi, 2024;Penner et al, 2022;Sengupta & Puri, 2022;Neff & Betz, 2017).…”
Section: Cultural Motherhood Economic Efficiency Opportunity Costs Ge...mentioning
confidence: 99%